The impact of COVID-19 on health care–associated infections in intensive care units in low- and middle-income countries: International Nosocomial Infection Control Consortium (INICC) findings. (May 2022) - Rosenthal, Victor D.; Myatra, Sheila Nainan; Divatia, Jigeeshu Vasishtha; Biswas, Sanjay; Shrivastava, Anjana; Al-Ruzzieh, Majeda A.; Ayaad, Omar; Bat-Erdene, Ariungerel; Bat-Erdene, Ider; Narankhuu, Batsaikhan; Gupta, Debkishore; Mandal, Subhranshu; et al.
Highlights: Due to the COVID pandemic, health care–associated infection rates increased in resource-limited countries. Due to the COVID pandemic, rates of central line–associated bloodstream infections increased. Due to the COVID pandemic, rates of central ventilator–associated events increased. Due to the COVID pandemic, mortality rates increased in intensive care units of resource-limited countries in 2020. Due to the COVID pandemic, average length of stay increased in resource-limited countries in 2020. ABSTRACT: Background: This study examines the impact of the COVID-19 pandemic on health care–associated infection (HAI) incidence in low- and middle-income countries (LMICs). Methods: Patients from 7 LMICs were followed up during hospital intensive care unit (ICU) stays from January 2019 to May 2020. HAI rates were calculated using the International Nosocomial Infection Control Consortium (INICC) Surveillance Online System applying the Centers for Disease Control and Prevention's National Healthcare Safety Network (CDC-NHSN) criteria. Pre–COVID-19 rates for 2019 were compared with COVID-19 era rates for 2020 for central line–associated bloodstream infections (CLABSIs), catheter-associated urinary tract infections (CAUTIs), ventilator-associated events (VAEs), mortality, and length of stay (LOS). Results: A total of 7, 775 patients were followed up for 49, 506 bed days. The 2019 to 2020 rate comparisons were 2.54 and 4.73 CLABSIs per 1, 000 central line days (risk ratio [RR] = 1.85, p = .0006), 9.71 and 12.58 VAEs per 1, 000 mechanical ventilator days (RR = 1.29, p = .10), and 1.64 and 1.43 CAUTIs per 1, 000 urinary catheter days (RR = 1.14; p = .69). Mortality rates were 15.2% and 23.2% for 2019 and 2020 (RR = 1.42; p < .0001), respectively. Mean LOS for 2019 and 2020 were 6.02 and 7.54 days (RR = 1.21, p < .0001), respectively. Discussion: This study documents an increase in HAI rates in 7 LMICs during the first 5 months of the COVID-19 pandemic and highlights the need to reprioritize and return to conventional infection prevention practices.